Faktor yang menentukan corporate social responsibility pada sektor perbankan yang terdaftar di BEI - Maryujati, Arini Giri; Leon, Farah Margaretha; Purba, Yosephina Endang (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the factors that influence corporate social responsibility in banking sector companies listed on the IDX during the period 2014-2020. The data used in this study is secondary data sourced from the official website of Indonesia Stock Exchange (IDX). The research sample was selected using a purposive sampling method so that 24 companies were sampled. The novelty in this research is to use the SCV formula for CSR and the addition of the board of commissioners variable. The results show that profitability, liquidity, firm size, leverage have a positive effect on corporate social responsibility. Board size has a negative effect on corporate social responsibility. Foreign director, female director, board of commissioners size has no effect on corporate social responsibility. This shows that big profitability, liquidity, company size, leverage can encourage CSR activities and become investors' considerations. The benefits of CSR activities are an important assessment for investors to invest their capital..